Delivering tourism intelligence : from analysis to action - Pearce, Philip L.; Oktadiana, Hera (Emerald Publishing Limited, 2019)
Tourism researchers are feeling mounting pressure to answer an increasing number of questions from external agents which challenge the ability of their findings to deliver tangible change. Delivering Tourism Intelligence demonstrates that good academic analysis can deliver quality implications for a range of stakeholders. Contributions from authors across the continents serve to illustrate ways in which academic analysis can, and does, result in action. The chapters in this volume are organised into three parts: governance, planning and sustainability; consumer benefits and experiences; and benefits to entrepreneurs. The chapter authors provide a rich array of examples and cases from Europe, Africa, Asia and Australia, all of which reveal that academic studies can play a strong role in fostering positive changes relevant to the needs of varied stakeholders. Key themes revolve around the need for stakeholder trust, the ability of researchers to use tools for insights, the value of identifying new trends and tourism topics, the importance of understanding target markets, the usefulness of universities and researchers for providing training, and an appreciation of the time it takes for some ideas to be implemented. With individual chapters which address hotel management, destination management, markets and community sustainability, as well as public policy topics, this book will appeal to postgraduates studying in these areas as well as those practitioners and policy makers working in applied sectors.
Includes index.
Keywords: Tourism -- Research.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books